EXAMINING ETHICAL FRAMEWORKS IN CONFLICT RESOLUTION STRATEGIES IN WORKPLACE SETTINGS: CHALLENGES AND BEST PRACTICES - Jorovlea, Elvira; Codreanu, Alina (SWorld-Ger Conference proceedings, 2024)
In today’s workplace, conflict is inevitable and can affect organizational effectiveness and employee morale. Understanding ethical frameworks—such as consequentialism, deontology, virtue ethics, and care ethics—is crucial to effective conflict resolutio